The Attractive Territory: Contribution of the Territorial Positioning and the Innovative Theoretical and Historical Models - Harroussi, Baha Eddine; Chakor, Abdellatif (European Scientific Journal, ESJ, 2019)
This paper focuses on all the classic strategies of positioning throughout history that certainly generates the concept of innovation to positioning policies. To this end, innovation takes its organizational concept to be adapted to the marketing issue especially to the territorial thing. This is for the purpose of constituting an attraction for the targets including economic activities. This attraction is not a permanent situation; on the other hand, the territory must consolidate its competitive state to build an attraction in its permanent notion. The mobile state of the economy, which encourages territories to be attractive and competitive, is explained by several concepts, including economic globalization and the fluctuation of capitals. In this paper, we will explain several notions of attractiveness with a broad presentation of both economic and territorial attractiveness concerning investments. For this purpose, positioning refers to an antecedent notion of attractiveness which is seen as a marketing process. It is aimed at adapting the territorial offer to the aspirations and motivations of investors and the impact and contribution of the innovative idea in the process.